2017
DOI: 10.1111/1744-7917.12499
|View full text |Cite
|
Sign up to set email alerts
|

Herbivore performance and plant defense after sequential attacks by inducing and suppressing herbivores

Abstract: It is well known that herbivore-induced plant defenses alter host plant quality and can affect the behavior and performance of later arriving herbivores. Effects of sequential attacks by herbivores that either suppress or induce plant defenses are less well studied. We sequentially infested leaves of tomato plants with a strain of the phytophagous spider mite Tetranychus urticae that induces plant defenses and the closely related Tetranychus evansi, which suppresses plant defenses. Plant quality was quantified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 65 publications
(150 reference statements)
0
20
0
Order By: Relevance
“…In soybean, damage by fall armyworm caterpillars increased the activity of PIs, whereas thrips damage did not [43]. De Oliveira et al [11] even observed varying response of tomato PIs to damage by herbivores of the same genus. They showed that PI activity was induced by the spider mite Tetranychus urticae, but was suppressed by T. evansi [11].…”
Section: Herbivore Specificity In Pnkti Inductionmentioning
confidence: 97%
See 1 more Smart Citation
“…In soybean, damage by fall armyworm caterpillars increased the activity of PIs, whereas thrips damage did not [43]. De Oliveira et al [11] even observed varying response of tomato PIs to damage by herbivores of the same genus. They showed that PI activity was induced by the spider mite Tetranychus urticae, but was suppressed by T. evansi [11].…”
Section: Herbivore Specificity In Pnkti Inductionmentioning
confidence: 97%
“…De Oliveira et al [11] even observed varying response of tomato PIs to damage by herbivores of the same genus. They showed that PI activity was induced by the spider mite Tetranychus urticae, but was suppressed by T. evansi [11]. Interestingly, feeding damage by lepidopteran and coleopteran herbivores in tomato yielded opposite results to our study in black poplar.…”
Section: Herbivore Specificity In Pnkti Inductionmentioning
confidence: 98%
“…T. urticae feeds on the epidermis and punctures parenchyma cells, leaving light‐colored stipples on the leaf surface and injecting phytotoxic compounds that reduce photosynthesis and decrease yield 37,38 . T. urticae activates both the JA and SA signaling pathways, which function differently in plant–arthropod interactions 15,28,39–41 . For instance, up‐regulation of plant defenses such as proteinase inhibitors and allelochemicals caused by T. urticae is correlated with significantly poor performances of the cucumber moth, Diaphania indica (Saunders) (Lepidoptera: Pyralidae), and the red spider mite, T. evansi Baker (Acari: Tetranychidae).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the ecological interactions between maize and T. urticae may be insufficient to make selection pressure to input evaluation of plant defense mechanisms. Furthermore, previous studies showed that 1 d of infestation is sufficient for the T. urticae to induce plant defenses (Kant et al 2004;Oliveira et al 2016Oliveira et al , 2017.…”
Section: Discussionmentioning
confidence: 99%
“…The treatments were 2 versions of Bt maize and non Bt; uninfested (= clean) plants; single infestation with spider mite; and dual species infestation with spider mite and fall armyworm for each maize version. Two d after the first infestation, all plants were re-infested with spider mite to evaluate the impact of previous infestations, because 1 d of infestation is sufficient for T. urticae to induce defense in other plants (Kant et al 2004;Oliveira et al 2016;Oliveira et al 2017). For initial infestation or re-infestation with T. urticae, 10 female T. urticae were introduced to the abaxial surface of a leaf within a barrier made with entomological glue Biocontrole® (Indaiatúba, São Paulo, Brazil) to avoid escape or wandering off.…”
Section: Infestation Of Plants and Biological Analysismentioning
confidence: 99%